On modeling OTA channel emulation systems - Lorenz, Mario; Kotterman, Wim; Galdo, Giovanni Del (IET Conference Publications, 2018)
One trend in Over-The-Air (OTA) testing is leaving hand held UE's behind and considering mobile stations, may include cars, trucks, trains, boats and even airplanes. For such physically large devices, state-of-the-art OTA testing approaches like Wave Field Synthesis do not scale well. In order to evaluate suitability of other novel approaches, a tensor based model for describing the channel emulation system is proposed. In this way, several other channel emulation methods can be described and classified. Hardware requirements can be compared, and measures to reduce the cost and complexity of the channel emulation system be studied.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Emulation; Modeling; OTA